Psychometric properties of a Korean version of the pre-sleep arousal scale - Namhee Kim; Bo Gyeong Lee (PLoS ONE, 2025)
Purpose Sleep quality is a multidimensional construct encompassing the effectiveness and restorativeness of sleep. The pre-sleep arousal scale is a widely used instrument for evaluating aspects of arousal that are closely related to sleep quality. This study aimed to evaluate the psychometric properties of the Korean version of the pre-sleep arousal scale (K-PSAS). Methods We performed a secondary analysis of cross-sectional data from 286 adults aged 19–70 years who used electronic cigarettes or heated tobacco products. The original PSAS was translated into Korean, with content validity assessed by experts. Construct validity was evaluated via exploratory factor analysis, and concurrent validity was assessed by correlating the K-PSAS with the Insomnia Severity Index, Pittsburgh Sleep Quality Index, and Hospital Anxiety and Depression Scale. Reliability was examined using Cronbach’s α, and split-half reliability coefficient. Results Both the item-level content validity index for all items and the scale-level content validity index average for the K-PSAS-16 were 1.0. After removing the survey item on “being mentally alert and active at bedtime” (item 13) due to low factor loading, the K-PSAS-15 demonstrated a two-factor structure, with somatic and cognitive arousal factors explaining 42.36% and 10.19% of the variance, respectively. A significant positive correlation was observed between the two factors (ρ = 0.61, p < .001). Item 13 also showed a low corrected item-total correlation coefficient of −0.10. The correlation coefficients between K-PSAS-15 and other validated scales ranged from 0.49 to 0.71. The K-PSAS-15 showed good internal consistency, with a Cronbach’s α of.91 for the total scale, and α = .87 and.90 for the somatic and cognitive subscales, respectively. Split-half reliability was also acceptable (total = .90; somatic = .86; cognitive = .88). Conclusion The K-PSAS-15, which excludes one poorly performing item from the original scale, is a reliable and valid tool for assessing pre-sleep arousal.